Long-Term Outcomes after Aortic Valve and Root Replacement in a Very High-Risk Population - Jan Hlavicka; Kiril Antonov; Razan Salem; Florian Hecker; Spiros Marinos; Medhat Radwan; Fabian Emrich; Arnaud Van Linden; Anton Moritz; Thomas Walther; Tomas Holubec (Journal of Cardiovascular Development and Disease, 2022)
Background: Aortic valve and root replacement (AVRR) is a standardised procedure to treat patients with aortic valve and root disease. In centres with a well-established aortic valve and root repair program (valve repairs and Ross operations), only patients with very complex conditions receive AVRR; this procedure uses a mechanical or biological composite valve graft (modified Bentall–de Bono procedure). The aim of the study was to evaluate the short- and long-term results after AVRR in a high-risk population with complex pathologies. Methods: Between 2005 and 2018, a total of 273 consecutive patients (mean age 64 ± 12.8 years; 23% female) received AVRR. The indication for surgery was an acute type A aortic dissection in 18%, infective endocarditis in 36% and other pathologies in 46% patients; 39% were redo procedures. The median EuroSCORE II was 11.65% (range 1.48–95.63%). Concomitant surgery was required in 157 patients (58%). Results: The follow-up extended to 5.2 years (range 0.1–15 years) and it was complete in 96% of the patients. The 30-day mortality was 17%. The overall estimated survival at 5 and 10 years was 65% ± 3% and 49% ± 4%, respectively. Univariate and multivariate logistic regression analyses revealed the following risk factors for survival: perioperative neurological dysfunction (OR 5.45), peripheral artery disease (OR 4.4) and re-exploration for bleeding (OR 3.37). Conclusions: AVRR can be performed with acceptable short- and long-term results in a sick patient population. The Bentall–De Bono procedure may be determined to be suitable for only elderly or high-risk patients. Any other patients should receive an AV repair or the Ross procedure in well-established centres.